2017
DOI: 10.1111/rda.12976
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian follicle development and genital tract characteristics in different birthweight gilts at 150 days of age

Abstract: In the last decades, selection for improved prolificacy has resulted in higher litter sizes and has thereby increased the proportion of low birthweight (LW) piglets. It is well documented that LW piglets have lower growth performance, muscle accretion and poor carcass quality. However, little is known about the relations of birthweight with subsequent reproductive performance in gilts. This study investigated the effects of birthweight on reproductive tract and ovarian follicle development in 150-day-old gilts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Gilts with a low birth weight are associated with intrauterine growth retardation [46], and have fewer medium size follicles and more atretic follicles on the ovary than gilts with a high birth weight, when approaching expected puberty age [47]. Therefore, gilts with a low birth weight should not be selected, nor should those born to sows that have farrowed a large litter with large variation in birth weights.…”
Section: Number Of Piglets Born Alive (Pba) In Paritymentioning
confidence: 99%
“…Gilts with a low birth weight are associated with intrauterine growth retardation [46], and have fewer medium size follicles and more atretic follicles on the ovary than gilts with a high birth weight, when approaching expected puberty age [47]. Therefore, gilts with a low birth weight should not be selected, nor should those born to sows that have farrowed a large litter with large variation in birth weights.…”
Section: Number Of Piglets Born Alive (Pba) In Paritymentioning
confidence: 99%
“…Within-litter variation has been attributed to factors such as the duration of ovulation, oocyte maturation, the implantation capability of conceptuses and position within the uterus, placental efficiency, uterine space, breed differences and intrauterine growth retardation [12]. There is consensus that low birth weight gilts have increased preweaning mortality [13,14] and those low birth weight gilts that do survive past the nursery phase have poor growth until finishing and are significantly lighter than their higher birth weight litter mates [13,15]. Additionally, as future replacement females, low birth weight negatively impacts their reproductive potential.…”
Section: Birth Traits That Determine the Efficiency Of Replacementmentioning
confidence: 99%
“…Additionally, as future replacement females, low birth weight negatively impacts their reproductive potential. Variation in birth weight is negatively correlated to ovarian and uterine development [16] and low birth weight gilts have different populations of follicles on the ovary and shorter vaginal length at 150 days of age, suggesting ovulation rate and consequently litter size may be adversely affected [15]. Collectively, the reports of Valet et al [17] and Calderon-Diaz et al [18] suggested that, in high health environments, the birth weight and overall growth rate of contemporary commercial gilts are not limiting for age at puberty, but preweaning growth rate was inversely related to age at puberty and birth weight was positively associated with uterine weight.…”
Section: Birth Traits That Determine the Efficiency Of Replacementmentioning
confidence: 99%
“…In recent years, focus on gilt development and sow longevity has identified litter of origin, birthweight, growth rate, and body composition as key factors. Almeida et al (2017b) reported that low birthweight gilts had different populations of follicles on the ovary when approaching expected age at puberty (Almeida et al, 2017a). In addition, low birthweight gilts have slower growth and often cannot achieve the target growth rate of 600 g/d at the time of selection (Kummer et al, 2009).…”
Section: The Physiology Of the Follicular Phase In Prepubertal Giltsmentioning
confidence: 99%